Keefektifan Media Pembelajaran Canva bermuatan Kearifan Lokal Surabaya dan Banyuwangi untuk Meningkatkan Keterampilan Menyimak Kelas III Sekolah Dasar - Hafadah, Nurul; Istiq’faroh, Nurul; Adibah, Adinda Putri Nur (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
This research is motivated by the low listening skills of elementary school students caused by learning that is still dominated by lecture methods and the lack of use of interactive and contextual learning media. In addition, the use of local wisdom in learning is also not optimal, so the material is not close to students' lives. This study aims to determine the effectiveness of interactive learning media based on Canva, which contains local wisdom of Surabaya and Banyuwangi, in improving the listening skills of third-grade students in an elementary school in the city of Surabaya. The method used is a descriptive quantitative study with a pre-experimental design in the form of a one-group pretest–posttest design. The research subjects numbered 10 students. Data collection techniques included observation, interviews, questionnaires, and tests. Data were analyzed using descriptive quantitative techniques by comparing the results of the pre-test and post-test to determine the improvement in students' listening skills. The results showed a significant improvement, with an average pre-test score of 51 increasing to 94 in the post-test. All students experienced improved learning outcomes after using the learning media. The Canva-based media developed was able to attract students' attention, increase their activeness, and help students understand the material more easily and meaningfully through visual and contextual presentation. Thus, Canva-based interactive learning media containing local wisdom has proven effective in improving elementary school students' listening skills and can be an innovative alternative in learning that integrates technology and local culture.